2021
DOI: 10.3390/cancers13205144
|View full text |Cite
|
Sign up to set email alerts
|

Brain and Breast Cancer Cells with PTEN Loss of Function Reveal Enhanced Durotaxis and RHOB Dependent Amoeboid Migration Utilizing 3D Scaffolds and Aligned Microfiber Tracts

Abstract: Background: Glioblastoma multiforme (GBM) and metastatic triple-negative breast cancer (TNBC) with PTEN mutations often lead to brain dissemination with poor patient outcome, thus new therapeutic targets are needed. To understand signaling, controlling the dynamics and mechanics of brain tumor cell migration, we implemented GBM and TNBC cell lines and designed 3D aligned microfibers and scaffolds mimicking brain structures. Methods: 3D microfibers and scaffolds were printed using melt electrowriting. GBM and T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 103 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…Additionally, it ranks among the most frequently deleted tumor suppressor genes in human cancer cells (Leslie and Downes 2004 ; Haddadi et al 2018 ). MDA-MB-231 cells express wild-type PTEN (Hlobilkova et al 2006 ; Wieland et al 2021 ). In addition, Razmara et al suggested that MKP-3 negatively modulates the PI3K-dependent AKT phosphorylation (Razmara et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it ranks among the most frequently deleted tumor suppressor genes in human cancer cells (Leslie and Downes 2004 ; Haddadi et al 2018 ). MDA-MB-231 cells express wild-type PTEN (Hlobilkova et al 2006 ; Wieland et al 2021 ). In addition, Razmara et al suggested that MKP-3 negatively modulates the PI3K-dependent AKT phosphorylation (Razmara et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] Moreover, U87 glioma cells resemble a skating snail phenotype due to durotaxis of aligned PCL fibers. [ 24 ] The term skating snail refers to quick changes in morphology from moving around toward long attached cells along the fibers and again scrolling. Even though the box design is more complex than the aligned linear PCL fibers, the morphology and behavior of U87 cells remained the same (Figure 1C; and Video S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies ( 27 - 29 ) have shown that mTOR is related to tumorigenesis and development and can control the expression of the c-myc gene, thereby controlling the transcription and translation of cellular ribosomal proteins. mTOR is highly expressed in prostate cancer and breast cancer tissues, which may be closely related to tumor formation and active cell proliferation.…”
Section: Discussionmentioning
confidence: 99%